Postoperative Coronavirus Disease 2019 Infection in a Patient with Recurrent Colon Carcinoma: First Surgical Case Experience in the Pandemic - Uludağ, Server Sezgin; Güreş, Nazım; Şanlı, Ahmet Necati; Balkan, İlker İnanç and Zengin, Abdullah Kağan (Cerrahpaşa Medical Journal, 2020)
Coronavirus disease 2019 (COVID-19) is a disease that can present in different ways depending primarily on the age, gender, presence of comorbidities, and immune status of the patients. In this report, we aimed to present the case of detection of postoperative COVID-19 infection in a patient with a diagnosis of recurrent colon tumor. This case was also the first surgical case of COVID-19 infection at the general surgery clinic of the oldest university hospital in Istanbul. A 73-year-old male patient underwent surgery owing to recurrent colon carcinoma. He did not have any known lung disease. Complementary colectomy, splenectomy, and liver metastasectomy were performed. He was discharged on postoperative day 8. However, the patient was admitted to the emergency room again the next day because of vomiting and abdominal distention. There were no active leakage findings on radiologic screening. Despite antibiotherapy, the patient continued to have high C-reactive protein levels during follow-up, and he also had a fever and respiratory difficulties. The findings on chest computed tomography scan indicated bilateral pneumonic infiltrations and acute respiratory distress syndrome. The patient tested positive for COVID-19 with the polymerase chain reaction test. Despite intensive care support, the patient died of COVID-19 pneumonia. Despite the COVID-19 outbreak, urgent surgical procedures and oncological surgeries continued to be performed. Many complications can be seen in oncological patients after surgical procedures. In this case, we saw that surgical complications and COVID-19 symptoms can overlap during the postoperative period. Cite this article as: Uludağ SS, Güreş N, Şanlı AN, Balkan İİ, Zengin AK. Postoperative Coronavirus Disease 2019 Infection in a Patient with Recurrent Colon Carcinoma: First Surgical Case Experience in the Pandemic. Cerrahpaşa Med J 2020; 44(3): 153-156.